THE ECCENTRIC DIGRAPH OF THE CORONA OF $Cn$ WITH $Km$, $Cm$ OR $Pm$ - Kuntari, Sri; Kusmayadi, Tri Atmojo (Journal of the Indonesian Mathematical Society, 2012)
pdf abstractDOI :Â http://dx.doi.org/10.22342/jims.18.2.117.113-118